STUDENTS’ RESPONSE ANALYSIS TOWARD THE USE OF INFOGRAPHIC-BASED LEARNING MEDIA IN REPRODUCTIVE BIOLOGY COURSE AT INDRAPRASTA PGRI UNIVERSITY - Utami, Cintara Prili Widya; Supardi U. S (PT. Antis International Publisher, 2025)
Objective: The shift to online learning during the COVID-19 pandemic presented significant challenges, particularly in delivering complex material such as Reproductive Biology, which involves abstract and visually rich concepts. Infographic-based learning media, which combines visual and textual data, has emerged as a promising solution to improve student comprehension. This study aims to analyze students’ responses toward the use of infographic media in learning organogenesis content. Method: A descriptive qualitative method was employed, involving 46 sixth-semester biology education students from Universitas Indraprasta PGRI. Data were collected through a Likert-scale questionnaire and analyzed qualitatively. Results: Results indicate that most students provided positive responses, highlighting the media’s role in enhancing understanding, supporting task completion, and fostering learning interest. Novelty: This media is recommended for broader application in both online and face-to-face learning.